Perbandingan Eufemisme Dan Disfemisme Dalam Berita Olahraga Di Media Youtube Metro Tv Dan CNN Indonesia Sebagai Bahan Ajar Teks Narasi Tingkat SMP Kelas IX - Wijayanti, Nuraini; Sugiarti, Dewi Herlina; Meliasanti, Ferina (Peneliti.net, 2024)
This research is motivated by a lack of understanding of polite language style or what is called euphemism and impolite language called dysphemism in online media that can be accessed by many audiences, both parents and children who are still underage. Therefore, this study aims to make a comparison regarding the use of euphemisms and dysphemism on social media such as on YouTube, especially on YouTube METRO TV and CNN Indonesia by looking at the speeches that discuss the 2022 AFF Cup expressed by hosts and guest stars. By using the theory from Allan Keith & Burridge (in Saifullah, 2018: 78-82), namely on the types of euphemisms and dysphemisms, there are 12 types consisting of: new modelling, phonetic similarities, acronyms, abbreviations, word games, circumlocutions, hyperboles , hidden statements, substitutions, synecdoche, and loanwords. The results of the study show that not all types of euphemisms and dysphemism exist on METRO TV and CNN Indonesia's YouTube media, so METRO TV's YouTube uses more types of euphemisms, namely there are 11 types of euphemisms and dysphemisms that are found to have new models, phonetic similarities, acronyms, abbreviations, puns, circumlocutions, hyperbole, hidden statements, metonymy, substitution, synecdoche, and loanwords. Compared to CNN Indonesia, only 9 types of euphemism and dysphemism were found, namely new modeling, phonetic similarity, abbreviation, circumlocution, hyperbole, hidden statement, substitution, and synecdoche. In addition, METRO TV uses more dysphemism than CNN Indonesia. This research can be used as teaching materials at the junior high school level, class IX.